1998
DOI: 10.1007/s100520050080
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive jet production with virtual photons in next-to-leading order QCD

Abstract: We present a next-to-leading order calculation for the virtual photoproduction of one and two jets in ep collisions. Soft and collinear singularities are extracted using the phase space slicing method. The collinear photon initial state singularity depends logarithmically on the mass of the virtual photon and is absorbed into the virtual photon structure function. An MS factorization scheme is defined similarly to the real photon case. Numerical results are presented for HERA conditions using the Snowmass jet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
152
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(162 citation statements)
references
References 13 publications
10
152
0
Order By: Relevance
“…To summarize this Section, we have shown that the cross section formulae for virtual and real photon production in hadronic collisions are intimately related in leading order O(α s ) as well as in next-to-leading order O(α For virtual photons, this singularity is replaced by a logarithmic dependence on the photon virtuality Q [20].…”
Section: (C) and 2(c)) Thementioning
confidence: 92%
“…To summarize this Section, we have shown that the cross section formulae for virtual and real photon production in hadronic collisions are intimately related in leading order O(α s ) as well as in next-to-leading order O(α For virtual photons, this singularity is replaced by a logarithmic dependence on the photon virtuality Q [20].…”
Section: (C) and 2(c)) Thementioning
confidence: 92%
“…The NLO QCD (O(α 2 s )) calculations used in the analysis presented here were computed using the program by Klasen, Kleinwort and Kramer [59]. The calculations use the phase-space-slicing method [60] with an invariant-mass cut to isolate the singular regions of the phase space.…”
Section: Next-to-leading-order Qcd Calculationsmentioning
confidence: 99%
“…58 Member of Łódź University, Poland. 59 Now at Department of Physics, Stockholm University, Stockholm, Sweden. 60 Also at Cardinal Stefan Wyszyński University, Warsaw, Poland.…”
Section: Introductionmentioning
confidence: 99%
“…Many calculations of jet photoproduction at NLO exist [40][41][42][43][44][45][46], all of which have been compared with each other and agree to within (5 − 10)% [46,47]. The calculation used here is that of Frixione and Ridolfi [40,41], which employs the subtraction method [48] for dealing with the collinear and infra-red divergences.…”
Section: Nlo Qcd Calculationsmentioning
confidence: 99%